Intermittent Obstruction Resulting from Multiple Intestinal Webs - Kristel Lobo Prabhu; Robert Enns; Carl J Brown (Canadian Journal of Gastroenterology)
Intestinal webs are a rare cause of bowel obstruction. A case of a 32-year-old man with multiple intestinal webs causing intermittent, partial bowel obstruction is described. The webs were initially detected with capsule endoscopy. The patient was treated with intraoperative endoscopy and balloon dilation. At early follow-up, no recurrence of his symptoms was evident.